Ways of the Implementation of the European Education Area Strategic Framework in the New EU Member States - Stumbrienė, Dovilė; Želvys, Rimantas (Socialinė teorija, empirija, politika ir praktika, 2025)
Almost a quarter of a century has passed since the European Union started to implement the Lisbon strategy (2000) and developed a common education policy for all the member states. The newest strategic document which defines the direction of education policy development is the European Education Area strategic framework (ET2030), which is to be implemented by the year 2030. In order to monitor the attainment of education policy goals, common goals are set for the member states. However, the EU member states have achieved different levels of socio-economic development and operate in different historical and cultural contexts. It is common practice to divide EU countries into old and new member states because the social and economic differences between the groups are most evident. Besides that, there are also differences within each group. Therefore, we may assume that the scope and the mode of achieving educational goals also differ. The study aims to reveal education policy differences of post-socialist EU member states. For this purpose, the most convenient strategy towards the ET2030 strategic framework has been identified for each post-socialist EU country, considering their different social, economic, and cultural situation.
Keywords: post-socialist EU countries; benchmarking analysis; education policy goals; ET2030 strategic framework